From Quantity to Quality: China’s International Student Strategy - Li , Ming; Ishikura, Yukiko (International Higher Education, 2025)
China’s international student strategy is shifting from enrollment-driven goals to a more diversified, quality-oriented model. Once focused on attracting degree students, recent efforts emphasize short-term international exchanges, and Chinese universities’ overseas programs and campuses. Challenges such as the COVID-19 pandemic, geopolitical tensions, and domestic criticism have spurred this reorientation. Despite policy ambiguity, emerging initiatives suggest a more flexible, outcome-driven approach aimed at strengthening global engagement and ensuring the long-term sustainability of international education in China.